2016
DOI: 10.1016/j.pedneo.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extracorporeal Membrane Oxygenation on Acute Fulminant Myocarditis-related Hemodynamic Compromise Arrhythmia in Children

Abstract: Hemodynamic compromise arrhythmia is common in AFM patients and may cause rapid deterioration. Simply correcting sinus rhythm is not always sufficient because of myocardium instability. Timely use of ECMO can improve the survival rate and shorten the time to recapture sinus rhythm in AFM patients with CAVB or VT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…[15] In a study on children with acute fulminant myocarditis, the overall patient survival rate was 78% (14/18), and three of the four nonsurviving patients died of VT and heart failure refractory to medical treatment. [19]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] In a study on children with acute fulminant myocarditis, the overall patient survival rate was 78% (14/18), and three of the four nonsurviving patients died of VT and heart failure refractory to medical treatment. [19]…”
Section: Discussionmentioning
confidence: 99%
“…A study on acute fulminant myocarditis in children revealed that timely use of extracorporeal membrane oxygenation (ECMO) can improve survival rates. [19] Our hospital does not have ECMO equipment. Finally, the validity of a prediction model should be verified by external data.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were published regarding ECMO in fulminant myocarditis . The first is a review of 8 cases of fulminant myocarditis requiring ECMO in children with a median age of 8 years .…”
Section: Discussionmentioning
confidence: 99%
“…Longer duration of ECMO support was associated with decreased survival. The second study is a retrospective review of 18 cases of fulminant myocarditis of which 16 (89%) had an arrhythmia at presentation . Seven children were supported with ECMO, and all survived.…”
Section: Discussionmentioning
confidence: 99%
“…VA ECMO may be ideal in the setting of refractory ventricular arrhythmias. If it is impossible to terminate or control severe ventricular arrhythmias, placing the patient on VA ECMO is a relatively simple solution, as long as there is a path forward (such as ablation or definitive therapy such as a heart transplant or a total artificial heart placement) [ 23 26 ]. One issue to consider is whether the ventricles will eject in the setting of refractory arrhythmias.…”
Section: Who Is a Candidate For Ecmomentioning
confidence: 99%